Pengaruh Erupsi Gunung Agung Terhadap Produksi Kerajinan Patung Di Desa Sebatu, Kecamatan Tegallalang, Kabupaten Gianyar - Ni Wayan Ririn Putri Darmayanti; Luh Putu Kerti Pujani (JURNAL DESTINASI PARIWISATA, 2019)
This research was conducted to determine the effect of Mount Agung eruption on the production of sculpture in Sebatu Village, Tegallalang District, Gianyar Regency. The types of data and sources of data used are qualitative, primary and secondary data. Data collection is conducted by observation, in-depth interviews and documentation. Analysis of the data used was qualitative data analysis to seek the relationship between the influence of the Mount Agung eruption on the qaunitity of sculpture production and the distribution network of sculpture crafts in Sebatu Village. The results of this study indicate that sculpture crafts produced in Sebatu Village are a type of contemporary sculpture that is dominated by animal statues. The production capacity of sculpture crafts in Sebatu village after the eruption of Mount Agung has increased, contrary to when the eruption occurred tourists could not come directly to order sculpture and their production capacity had declined. The working system of sculpture craftsmen has started to run normally with increasing production capacity. The distribution network of sculpture crafts in Sebatu Village can be distributed in five ways through distribution to the Sukawati art market, Balinese souvenirs, shipping by sea, shipping via cargo and distribution to the villa. From the conclusion, the Gianyar Regency Government should provide capital support for the sculpture industry, especially in Sebatu Village, Tegallalang District.There is a need to increase capital for handicraft business owners by providing financial or credit assistance for sculpture.Thus, there will be many entrepreneurs who are growing and increasing their production. Keywords: Statue Craft, Mount Agung Eruption, and Distribution Network.